Pengalaman menyusui pada ibu remaja: a scoping review - Annisa Rusdi; Dewi Rokhanawati; Intan Mutiara Putri (Universitas Aisyiyah Yogyakarta, 2021)
The coverage of breastfeeding in adolescent mothers was lower and the average duration of breastfeeding was shorter than the adult mothers. Adolescent mothers undergo the transition stages of becoming parents and adults simultaneously, which poses challenges to the breastfeeding process. The aim of this review was to discover the experience of breastfeeding in adolescent mothers. The scoping review method adapted the Arksey and O'Malley framework. There were 11 out of 562 articles selected based on inclusion and exclusion criteria. The experience of breastfeeding in adolescent mothers was described in three themes, namely breastfeeding decision making, factors that support breastfeeding and obstacles during breastfeeding